Custom and Order Batik Application System (COBS) - Halid, Nur Syuhada; Hussein, Idyawati; Ahmad, Mazida (Multidisciplinary Applied Research and Innovation, 2023)
Batik in general is a very delicate thing to make and design. As the design of batik keep on evolving throughout the years the same goes for the buyer where many of them want to create a new and unique batik design for themselves. So, the problem resulting to this project development is that batik buyers are having a hard time in specifying their needs and preferred batik design to the batik seller. This research aims to design and develop a custom and order function within a mobile batik identification application. Thus, the project objective is to provide a more efficient platform for the customer to express their needs regarding their preferred batik design where they can custom the batik design by themselves using the tools provided in the application system. Then, the methodology selected for this project development is Rapid Application Development (RAD) model and it includes 4 phases of management strategy. Through previous research we can see that it is more beneficial for all the business industries to improve their business operation through digital implementation. Compatible with the previous research, this project findings indicates that though digital implementation which in this case is the COBS do help improve the batik seller business operation mainly through customer satisfaction. In conclusion, COBS help improve the customer buying batik experience. This project help contributes a better alternative through digital implementation for all the clothing business entrepreneurs to further improve their business operation.